Estimating Victimization Rates, Trends and Risk Factors in Palestine - Mahmoud Okasha; Nisreen NouralDin (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This paper examines different risk factors that are most influential in identifying potential victims who have the greatest risk to be victimized in Palestine. The goal of this is to introduce a powerful statistical model that can be used in estimating the prevalence rates, trends and risk factors for a specific phenomenon such as victimization in Palestine as well as in other similar phenomena.  The risk factors for being victimized in Palestine including many demographic, economic and social variables have been studied. The goal is to find those significant risk factors and identify the characteristics of the persons who are prone to tangible losses. The data used in the analysis cover all the Palestinian Territories including the West Bank, Gaza Strip and East Jerusalem as of 2008 and has been gathered by the Palestinian Central Bureau Of Statistics. Logistic regression model has been used in the analysis, and revealed that the significant influential factors on victimization are sex and owning a car. The effects of each factor, its odds ratio and risk ratio are examined. The model has been applied to estimate the probability of a person to be victimized and to classify the persons who are vulnerable to be victimized, and succeeded in correctly classifying 64% of people who have really fallen victims and 96% of people who are unbeatable to crime. The general percentage of correct classification was 93.5%.